A review of complement sources used in serum bactericidal assays for evaluating immune responses to meningococcal ACWY conjugate vaccines. Issue 10 (3rd October 2019) - Findlow, Jamie; Balmer, Paul; Borrow, Ray
ABSTRACT: Invasive meningococcal disease is rare and potentially devastating but often vaccine-preventable. Evaluation of meningococcal vaccine effectiveness is impractical owing to relatively low disease incidence; protection is therefore estimated using serum bactericidal antibody (SBA) assays. Original experiments on natural immunity established a titer of ≥4 as the correlate of protection for SBA assays using human complement (hSBA), but human complement is relatively difficult to obtain and standardize. Use of baby rabbit complement (rSBA assays), per standard guidelines for serogroups A and C, generally results in comparatively higher titers. Postlicensure effectiveness data for serogroup C conjugate vaccines support acceptance of rSBA titers ≥8 as the correlate of protection for this serogroup, but no thresholds have been formally established for serogroups A, W, and Y. Studies evaluating MenACWY-TT (Nimenrix®; Pfizer Inc, Sandwich, UK) immunogenicity have used both hSBA and rSBA assays, and ultimately suggest that rSBA may be more appropriate for these measurements.